PENGGUNAAN WHO WHEEL CRITERIA DAN ALAT BANTU PENGAMBILAN KEPUTUSAN (ABPK) DALAM PEMILIHAN KONTRASEPSI PASCA PERSALINAN - Herlyssa Herlyssa Herlyssa; Sri Mulyati; Mardiana Dairi (Poltekkes Kemenkes Jakarta III, 2014)
WHO Wheel Criteria and ABPK is a counseling tool of Family Planning. WHO Wheel is a tool that has been adapted by Medical Eligibility Criteria Indonesia fromthe WHO in 2009 This study aims to determine the effect of the use of the WHO Criteria Wheel with postpartum contraception election. This research is a quasiexperimental design. Sampel research is third trimester pregnant women totaling 46 respondents consisting of 23 treatment group and a control group of 23 respondents. The treatment was done 2 times the third trimester of pregnancy and post partum while. The results showed the proportion of respondents choosing contraception that suits his condition was 69.9%, whereas that does not comply with the conditions of the clients of 30.1%. There is no difference in the proportion of highly educated mothers, age and working mothers in the treatment group and the control group. There is no effect of the use of the WHO Criteria Wheel on the conformity election postpartum contraception. So that the provider can still use both these tools in counseling of Family Planning.